Conservation of animal–plant mutualistic networks is essential to prevent functional extinction of the narrow endemic morning glory Ipomoea cavalcantei in Amazon canga ecosystems - Babiychuk, Elena; Teixeira, Juliana Galaschi; Tyski, Lourival; Imperatriz-Fonseca, Vera L.; Kushnir, Sergei (Frontiers in Ecology and Evolution, 2025)
Current studies of animal–plant mutualistic interaction networks and species climate change resilience call for redesigning biodiversity conservation management toward preventing species coextinction cascades and using interspecific hybridization as a species conservation tool. The upgrade of conservation management is urgent for narrow endemic plant species highly vulnerable to habitat destruction and defaunation. Ipomoea cavalcantei is a red-flowered, self-incompatible, narrow endemic morning glory confined to Amazon savanna-like ecosystems known as canga. Mining cangas reduces I. cavalcantei range, population sizes, and standing phenotypic variation. Here, we advance our understanding of the pollinator network that sustains I. cavalcantei reproductive success and interspecific gene flow. We show that ello sphinx, Erinnyis ello, is a new flower visitor in our model foraging nectar on I. cavalcantei and sister species Ipomoea marabaensis in cangas. We describe legitimate visiting of I. marabaensis flowers by the long-billed starthroat hummingbird, Heliomaster longirostris. On artificial flower displays, hawkmoths and hummingbirds readily foraged on the magenta-colored flowers of I. cavalcantei × I. marabaensis natural hybrids. Thus, a new pollinator, the ello sphinx, and previously unknown Ipomoea–hummingbird interactions may sustain interspecific gene flow that could enhance the species’ adaptive potential and be considered a conservation tool. Our results suggest that the overall reproductive success of I. cavalcantei is likely dependent on the long-billed hummingbird species. To avoid functional extinction, e.g., reduced genetic diversity due to pollinator loss, conservation must include assessing and monitoring the abundance and richness of hummingbird species at fragments of the remaining historical range and new introduction sites.